Иммунологические маркёры химиоиндуцированной нейротоксичности при гемобластозах у детей - Bazarny, V. V.; Kovtun, O. P.; Koryakina, O. V.; Fechina, L. G.; Polushina, L. G.; Maksimova, A. Yu.; Kopenkin, M. A. (Патогенез, 2022)
Тезисы конференции